2009
DOI: 10.1115/1.3077647
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Oxygen-Enriched Diesel Combustion Using Simulated Exhaust Gas Recirculation

Abstract: The techniques of design of experiments were applied to study the best operational conditions for oxygen-enriched combustion in a single-cylinder direct-injection diesel engine in order to reduce particulate matter (PM) emissions, with minimal deterioration in nitrogen oxide (NOx) emissions, by controlling fuel injection timing, carbon dioxide (CO2) and O2 volume fractions in intake air. The results showed that CO2 addition reduced average combustion temperatures and minimized the rate of increase in NOx emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Perez et al used CO 2 instead of EGR to study the variation of NO-smoke in oxygen-enriched diesel engines. The results showed that the best NO-smoke trade-off relationship can be achieved with 23% O 2 –10% CO 2 , but the advantages of oxygen-enriched combustion in CO, HC, and BSFC were completely canceled out . In conclusion, the existing literature on the reduction of NO x and particle emissions from oxygen-enriched engines is focused on diesel engines, and both H 2 O and inert gas are difficult to achieve excellent results in terms of both power and emissions performance.…”
Section: Introductionmentioning
confidence: 93%
“…Perez et al used CO 2 instead of EGR to study the variation of NO-smoke in oxygen-enriched diesel engines. The results showed that the best NO-smoke trade-off relationship can be achieved with 23% O 2 –10% CO 2 , but the advantages of oxygen-enriched combustion in CO, HC, and BSFC were completely canceled out . In conclusion, the existing literature on the reduction of NO x and particle emissions from oxygen-enriched engines is focused on diesel engines, and both H 2 O and inert gas are difficult to achieve excellent results in terms of both power and emissions performance.…”
Section: Introductionmentioning
confidence: 93%
“…There are some similar experimental studies. For example, Perez et al carried out an experimental study on diesel combustion using simulated recirculated exhaust gas [22]. They found that the addition of CO 2 reduced the average combustion temperature, and oxygen-enriched conditions improved the combustion process of internal combustion engines under O 2enriched conditions.…”
Section: Introductionmentioning
confidence: 99%
“…% with a quadratic function relationship between the flame velocities and the O 2 concentration . Compared with N 2 , the high concentration of CO 2 decreased the flame speeds and the measured flame speed using CO 2 as a diluent was about one-fifth of that using N 2 as a diluent. , From the open literature on the statistical analysis side, which merge the combustion technique along with the statistical analysis, Perez and Boehman investigated experimentally the oxygen-enriched diesel combustion using simulated exhaust gas recirculation. They measured the effect of exhaust gas recirculation on the particulate matter emissions and NOx emissions.…”
Section: Introductionmentioning
confidence: 99%